Analysis of Entrepreneurial Competency, Family Support For Entrepreneurial Interest Among Vocational High School Students In Mojokerto With Social Environment As A Mediating Variables - Setyowati, Eko Mety; Eka Ananta Sidharta; Agus Sumanto (International Journal of Technology and Education Research, 2025)
This study aims to analyze the influence of entrepreneurial competence and family support on entrepreneurial interest among vocational high school (SMK) students in Mojokerto, with social environment as a mediating variable. The background of this study is based on the importance of fostering entrepreneurial interest from an early age to encourage the creation of an independent and innovative young generation, as referred to in the Theory of Planned Behavior (TPB). The research method used a quantitative approach with Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis technique. The research sample consisted of 356 vocational high school students in Mojokerto who were selected purposively. The data collection instrument was a questionnaire with a Likert scale that measured the variables of entrepreneurial competence, family support, social environment, and entrepreneurial interest. The results of the analysis showed that entrepreneurial competence had a positive and significant effect on entrepreneurial interest. Family support was also proven to have a positive and significant effect on entrepreneurial interest. In addition, the social environment acts as a mediating variable that strengthens the influence of entrepreneurial competence and family support on students' interest in entrepreneurship. These findings confirm that a combination of internal factors (entrepreneurial competence), external factors (family support), and social interaction (social environment) are important elements in building interest in entrepreneurship among vocational high school students. The practical implications of this study are the need to strengthen entrepreneurship learning programs in schools, tangible support from families, and the creation of a conducive social environment to encourage the growth of an entrepreneurial spirit among the younger generation